CONCEPTS AND IMPLEMENTATION OF STATE FINANCE DURING THE ERA OF THE RIGHTLY GUIDED CALIPHS (AL-KHULAFĀ’ AL-RĀSHIDŪN) - Casnadi Casnadi (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the concept of state finance during the era of al-Khulafā’ al-Rāshidūn, examine the sources of state revenue and expenditure, and explore the fiscal policies implemented by the Rightly Guided Caliphs in managing public finance. The research employs classical Islamic public finance literature as primary sources, namely Kitab al-Amwāl by Abū ‘Ubaid, Kitab al-Kharāj by Abū Yūsuf, and al-Aḥkām al-Sulṭāniyyah by al-Māwardī. Secondary sources consist of authoritative works of Islamic jurisprudence from the four Sunni schools of law, classical Qur’anic exegesis, and major hadith compilations. This study adopts a qualitative approach using text-based content analysis by critically examining classical scholars’ discussions on state revenue and expenditure management during the period of al-Khulafā’ al-Rāshidūn. The findings reveal that the state played a crucial role in promoting public welfare through just financial governance grounded in the principle of maṣlaḥah (public interest). State revenue sources during this period included zakat, infaq, sadaqah, waqf, ‘ushūr, jizyah, kharāj, ghanīmah, and fay’. Meanwhile, state expenditures were allocated to public officials’ salaries, military allowances, pensions for veterans, defense budgets, infrastructure development, Islamic propagation, education, and social welfare programs. This study highlights the relevance of classical Islamic public finance principles in addressing contemporary fiscal governance challenges.